(untitled) (Revista de Biología Marina y Oceanografía, 2021)
Gracilaria chilensis is distributed in New Zealand (including Chatham Island) and South America. This species has a three-stage sexual life cycle, as well as asexual and vegetative reproduction, and is commercially important as it is a valuable source for producing agar. However, basing the crops exclusively on clonal reproduction and vegetative propagation has led to a reduction in their genotypic diversity, an increase in their susceptibility to infection by epiphytes, and a decrease in their quality. Thus, it is important to establish indoor cultures of G. chilensis from thalli with a mixed reproductive regime (sexual and asexual) that maintains the genetic variability of the cultivars. In this study, the biomass, growth rate, and productivity of indoor cultures of G. chilensis were evaluated (as a first approach) using various culture media (i.e., von Stosch medium (VS), Basfoliar® Aktiv (BF), and mixtures of VS and BF, namely, VS/BF-A and VS/BF-B). The VS/BF-A medium showed the best results in terms of biomass (51.8 ± 3.7 g m–2), growth rate (4.55 ± 0.43 %d–1), and productivity (14 g m–2 d–1), including the occurrence of thalli with cystocarps. The positive results using the VS/BF-A medium could be attributed to the fact that BF provides different elements (K, Cu, Mo, and Zn) that are crucial, since they are involved in numerous physiological functions in the algae, and also to the N:P ratio utilized (1:1), which positively affects growth and productivity. This information provides pivotal updated knowledge regarding cultures of G. chilensis under controlled conditions, promoting its successful cultivation for productive purposes.